State of the Art Review: Depression, Stress, Anxiety, and Cardiovascular Disease - Cohen, Beth E.; Edmondson, Donald; Kronish, Ian M. (American journal of hypertension, 2015)
The notion that psychological states can influence physical health is hardly new, and perhaps nowhere has the mind-body connection been better studied than in cardiovascular disease (CVD). Recently, large prospective epidemiologic studies and smaller basic science studies have firmly established a connection between CVD and several psychological conditions, including depression, chronic psychological stress, posttraumatic stress disorder (PTSD), and anxiety. In addition, numerous clinical trials have been conducted to attempt to prevent or lessen the impact of these conditions on cardiovascular health. In this article, we review studies connecting depression, stress/PTSD, and anxiety to CVD, focusing on findings from the last 5 years. For each mental health condition, we first examine the epidemiologic evidence establishing a link with CVD. We then describe studies of potential underlying mechanisms and finally discuss treatment trials and directions for future research.